MAJOR VASCULAR SURGERY IN THE GERIATRIC POPULATION: CARDIAC RISK STRATIFICATION - Perić, Velimir; Stošić, Marija; Stojanović, Dalibor; Lilić, Jelena; Nikolić, Nemanja; Lazović, Lela; Spasić, Dimitrije; Stojanović, Stefan; Lazarević, Milan (Srpski medicinski časopis Lekarske komore, 2022)
Reliance on surgery, improvements in surgical techniques, and perioperative management have led to a dramatic increase in the frequency of surgical procedures in the elderly population. According to the European Society of Cardiology and the European Society of Anaesthesiology and Intensive Care, major vascular surgery is defined as high-risk, considering the frequency of myocardial infarction and cardiac arrest, which is higher than 5%. Age is an independent predictor of myocardial infarction and cardiac arrest. Heart function alterations are primary changes that occur with advancing age. Risk stratification represents a set of procedures that include identifying chronic systemic diseases, determining their severity, stability and the need for further evaluation and/or therapy optimization, with the aim of reducing perioperative and postoperative mortality and morbidity. In addition to the application of risk scores, accurate risk stratification requires the combined application of both preoperative and postoperative biomarkers. The main idea of integrating biomarkers with scoring systems is to reveal those patients with clinically unmanifested disease, who carry a mortality risk and remain undetected by scoring systems. Biomarkers, such as NT-proBNP and highly sensitive C-reactive protein, have the greatest predictive influence in geriatric vascular surgery.